TNF-a (-238G/A and -308G/A) gene polymorphisms may not contribute to the risk of ischemic stroke. (3rd March 2016) - Gu, Lian; Wu, Guangliang; Su, Li; Yan, Yan; Liang, Baoyun; Tan, Jinjing; Cai, Haiyan; Jiang, Haiyun; Wei, Qiugui; Shen, Tingting; Wei, Ailing
Abstract : Background : The common and major pathological change in ischemic stroke is atherosclerosis in the artery. Tumor necrosis factor-a ( TNF-a) is closely related to the pathogenesis of atherosclerosis. The aim of our study was to investigate whether TNF-a gene variants (-238G/A and -308G/A) are associated with ischemic stroke. Methods : A total of 619 ischemic stroke patients and 612 controls were recruited to estimate the frequencies of two TNF-a (-238G/A and -308G/A) single nucleotide polymorphisms using a Sequenom MassARRAY time-of-flight mass spectrometer. The association between TNF-a gene polymorphisms and ischemic stroke risk was evaluated by computing the odds ratio (OR) and 95% Confidence Interval with multivariate unconditional logistic regression analyses. Results : The OR results indicated that no significant associations were found between TNF-a gene (-238G/A and -308G/A) polymorphisms and the risk of ischemic stroke using five genetic models, including the allele model (A vs. G), co-dominant model 1 (GA vs. GG), co-dominant model 2 (AA vs. GG), the dominant model (AA+GA vs. GG), and the recessive model (GG+GA vs. AA). Conclusions : The TNF-a (-238G/A and -308G/A) gene polymorphisms may not be a susceptible predictor of ischemic stroke in Chinese populations.